Prognostic Role of the C-Reactive Protein/Albumin Ratio in Patients With Gynecological Cancers: A Meta-Analysis - Fang, Yingji; Zheng, Tingting; Zhang, Chengling (Frontiers in Oncology, 2021)
Background Many studies have investigated the prognostic role of the C-reactive protein/albumin ratio (CRP/Alb ratio) in patients with gynecological cancers; however, there is lack of consensus owing to conflicting results across studies. We performed a meta-analysis to determine the prognostic role of the CRP/Alb ratio in gynecological cancers. Methods We searched the PubMed, Embase, the Web of Science, Cochrane Library, China National Knowledge Infrastructure, and Wanfang electronic databases since inception to April 2021. Combined hazard ratios (HRs) and 95% confidence intervals (CIs) were used to estimate the prognostic effect of the CRP/Alb ratio in gynecological cancers. Pooled odds ratios (ORs) and 95% CIs were used to investigate the association between the CRP/Alb ratio and clinicopathological features. Results The meta-analysis included seven studies with 1,847 patients. The pooled results showed that a high pretreatment CRP/Alb ratio was associated with poor overall survival (HR, 1.84; 95% CI, 1.41–2.40; p < 0.001) and progression-/disease-free survival (HR, 2.58; 95% CI, 1.42–4.68; p = 0.002). Additionally, a high CRP/Alb ratio was significantly associated with stages III–IV disease (the International Federation of Gynecology and Obstetrics classification) (OR, 2.98; 95% CI, 1.45–6.14; p = 0.003). However, we observed a non-significant correlation between the CRP/Alb ratio and lymph node metastasis, tumor size, and histopathological grade. Conclusions The CRP/Alb ratio is a convenient and accurate predictor of survival outcomes in gynecological cancers. A high CRP/Alb ratio also predicts tumor progression.